Increasing students' higher-order thinking skills: The power of project-based STEM in Ethnomathematics Learning - D.S., Suprojo; Sutama, Sutama; Fauziati, Endang; Markhamah, Markhamah (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to test the effectiveness of integrating STEM into project-based ethnomathematics learning to improve students' higher-order thinking skills (HOTS). A quantitative experimental design was used, involving 124 students from four junior high schools in Grobogan Regency. Data were collected using a test instrument based on HOTS indicators and processed using ANOVA after meeting prerequisites. The results show that STEM integration in project-based ethnomathematics significantly enhances students' HOTS. There was a significant difference in HOTS achievement among the four research groups after the intervention. Post Hoc tests with Tukey's HSD revealed that students exposed to project-oriented STEM had the highest average HOTS achievement compared to other groups. These students completed all HOTS stages, including analyzing (C4), evaluating (C5), and creating (C6). In contrast, students taught with conventional methods generally reached only the analysis stage (C4) and did not progress further. This condition shows that project-based STEM has the power to increase students' HOTS in ethnomathematics learning.